1997
DOI: 10.1128/jb.179.24.7724-7733.1997
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of envelope stress in Escherichia coli by the Cpx two-component system

Abstract: Disruption of normal protein trafficking in the Escherichia coli cell envelope (inner membrane, periplasm, outer membrane) can activate two parallel, but distinct, signal transduction pathways. This activation stimulates the expression of a number of genes whose products function to fold or degrade the mislocalized proteins. One of these signal transduction pathways is a two-component regulatory system comprised of the histidine kinase CpxA and the response regulator, CpxR. In this study we characterized gain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
377
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(399 citation statements)
references
References 71 publications
(120 reference statements)
21
377
1
Order By: Relevance
“…It encodes a small, stress-combative periplasmic protein capable of negatively regulating the Cpx response (12)(13)(14). In this study, we provide evidence that CpxP is degraded by the periplasmic protease DegP, together with misfolded PapE or PapG.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…It encodes a small, stress-combative periplasmic protein capable of negatively regulating the Cpx response (12)(13)(14). In this study, we provide evidence that CpxP is degraded by the periplasmic protease DegP, together with misfolded PapE or PapG.…”
mentioning
confidence: 60%
“…All strains were grown in Luria broth (LB) at 30°C unless otherwise indicated. Strains containing the cpxA24 allele were maintained on LB agar containing amikacin (Sigma) at 1.5 g͞ml (13). Plasmid-containing strains were grown in either ampicillin (Sigma) or chloramphenicol (Sigma) at concentrations of 125 g͞ml and 20 g͞ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins were either directly stained with Coomassie brilliant blue or transferred to nitrocellulose, stained with acidic Ponceau S and subjected to Western blot analysis. Rabbit polyclonal antibody raised against a maltosebinding protein (MBP)-CpxR hybrid (Raivio & Silhavy, 1997) was used at a 1 : 30 000 dilution and revealed with horseradish-peroxidaseconjugated goat anti-rabbit IgG (Bio-Rad). Enhanced chemiluminescence reagents were purchased from Pierce and used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A positive feedback, for example, can account for the stabilization, amplification, or prolongation of the outputs in the course of a signaling cascade. In fact, the feedback loops have been reported in two-component systems with some transcriptional factors looping downstream of the signaling pathways (13)(14)(15). However, the issue of whether ligand recognition or the ligandbinding affinity of sensory histidine kinases is directly modulated by such a feedback loop remains unclear, because few ligandbinding studies for other two-component sensory histidine kinases have been reported because of the experimental difficulties of measuring their binding affinities.…”
mentioning
confidence: 98%